Analisis Prioritas Pengembangan Pariwisata di Desa Wisata Lebih, Kecamatan Gianyar, Kabupaten Gianyar - Melia Sumitapradja, Annisa; Anom, I Putu (JURNAL DESTINASI PARIWISATA, 2020)
Lebih Village is a village located in Gianyar subdistrict, Gianyar regency, famous for its coastal tourism, which is Lebih Beach. Lebih Village have been included in the criteria for Tourism Village, however, their certificate has not been issued for this year. In addittion to the coastal tourist attraction, it turns out that the village has more potentials to be developed into a tourist attraction. Theses potentials include a natural, cultural and artificial attraction. These potentials still need to be developed in order to run in the tourism sector. In connection with this, the author tries to examine the “Analisis Prioritas Pengembangan Pariwisata di Desa Wisata Lebih, Kecamatan Gianyar, Kabupaten Gianyar. The research method used in this research is qualitative research with qualitative descriptive analysis technique and SWOT analysis, to analyze the tourism development priorities in Lebih tourism village. The purpose of this study was to determine how the existing conditions and to find out the priority strategies for tourism development in Lebih Village. Sources of data from primary data and secondary data, data collection techniques using observation, interview and literature study, and interview instruments in the form of interview guidelines. The research of informant in Lebih Tourism Village in this research use purposive sampling technique, to get accurate data about tourism development priorities in Lebih tourism village, Gianyar subdistrict, Gianyar regency. The conclusion of this research is the exisiting condition in Lebih Village with component 4A which explains the attractions, accsess, facilities, and additional services. In addition there is a main priority strategy for tourism development in Lebih Village which is to develop the potentials they have, collaborate with another stakeholders, conduct training for the community, build tourism facilities, conduct promotions and improve management. The results of this research is the strategies obtained by the SWOT analysis, which were used as a priorities development strategy of tourism in Lebih Tourism Village, Gianyar. Keyword: Tourism Development Periorities, SWOT analysis, Tourism Village, Lebih Village